Cyberdefense and its global and specific dimensions in the Spanish National Security Strategy (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The 2013 Spanish National Security Strategy includes cyberattacks as one of the threats which Spain is exposed to, and which according to the defined strategy routes, Spain will have to face to. Nevertheless, cyberthreats analysis cannot be done disconnectedly from those threats which are, also included in the document. On the opposite, most part of the threats mentioned in the ESN, are able to turn up through a cyberattack, so a global perspective, analyzing the subject, is due. A new question arises from this analysis, in the sense of having in mind when a ciberattack becomes a threat for Defense instead of a threat for security. A legal perspective will be the only proper way to settle when a cyberattack could be considered as a use of force, in order to answer the former question.
Keywords: Spanish National Security Strategy; cyberthreats; Defense; use of force